Dynamic Patent Races with Risky Choices - Park, Jaesun (Management Science, 1987)
This paper investigates equilibrium R&D investment strategies of firms endowed with different innovation potentials. To address this issue, this paper permits two stages of innovation and develops a simple stochastic game model involving two firms. It is shown that in equilibrium, a leader in the multiple stage innovation game invests more than a follower; firms compete more vigorously in the later stages of innovation than in the earlier stages; and a follower is more likely to choose a riskier innovation path than one requiring, on average, equivalent effort. It provides an explanation of how the expected benefits, the cost of R&D, and interactions between competing firms combine to determine dynamic R&D strategies over time.